Parental Knowledge, Attitudes, and Self-Efficacy in Pediatric First Aid in Tabuk City, KSA - Jesusa V. Gutierrez; Abdulaziz Alshehri; Talal Albalawi; Nawaf Alshehri; Mohmmed Asiri; Hasan Alatawi (European Scientific Journal, ESJ, 2025)
Background: First aid (FA) is the initial care provided for an acute illness or injury. This study aimed to determine the impact of parents' knowledge, attitude, and self-efficacy on pediatric first aid in Tabuk City.  Methods: A descriptive cross-sectional design study was conducted among 527 parents in Tabuk City. The participants completed a validated online questionnaire comprising 10 demographic questions, 25 knowledge questions, 11 questions on attitude, and 11 questions on parents’ self-efficacy concerning pediatric first aid. Results: Most participants were females (76%) between the ages of 41 and 50 (34%). A total of 97% were Saudi, and 79% had a high level of education (university or higher). The majority of participants were knowledgeable about first aid. The results also indicated that most parents have an appropriate attitude toward pediatric first aid. Finally, the parents’ self-efficacy revealed acceptable to high self-efficacy levels concerning pediatric first aid. Parents were confident and showed the necessary self-efficacy in nine out of 11 parts. Conclusion: Based on the present study’s findings, most parents in Tabuk City, Saudi Arabia, have basic knowledge of but limited experience with first aid. However, they are willing to improve their competence to ensure their household members, especially children, are safe from injuries and complications.